An extract of zanthoxylum rhetsa and use thereof - Shaari, Khozirah; Santhanam, Rameshkumar; Rukayadi, Yaya; Abas, Faridah; Ismail, Intan Safinar; Ahmad, Syahida (2014)
The present invention relates to an extraction of compounds from Zanthoxylum rhetsa (Z. rhetsa) and use of the compounds in preventing and reducing aging. The Z. rhetsa is subjected to solvent extraction and further undergoes the process of liquid-liquid partitioning to obtain the compounds. The resultant compounds are found to have effects as UV absorbers and to reduce aging.